Habitat prediction model for three-toed woodpecker and its implications for the conservation of biologically valuable forests. - Stachura-Skierczyńska, K.; Skierczyński, M.; Tumiel, T. (My University, 2009)
We studied habitat selection of three-toed woodpecker (TTW) in relation to forest structural variables, habitat types and hydrological conditions in north-eastern Poland. Based on known locations of 34 breeding pairs and the data on location of forest areas with high conservation value (referred to as Biologically Important Forests), we created a habitat prediction model for TTW using a Maxent algorithm. We found that this species most often selected breeding sites characterized by high contribution of old-growth stands with uneven vertical structure and considerable amount of very old trees of previous generations, as well as boreal spruce-dominated bogs and riverine forests. Such sites were preferred regardless of their actual protection status, which leads to the following conclusion: although existing forest reserves are very important to three-toed woodpecker, suitable habitats with similar characteristics can still be found outside protected areas and are also utilized by the species. However, such sites outside reserves are threatened by fragmentation due to timber extraction. Therefore it is recommended to protect these sites by either including them into existing reserves or putting them under special management schemes. The presented model can be applied in similar environmental conditions across lowland Europe, allowing for identification of representative habitat network for future conservation planning at landscape scale.
Keywords: Three-toed woodpecker; Habitat selection; Maxent